2018
DOI: 10.1097/md.0000000000013733
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of MIC1/GDF15 correlated with bone erosion in spondyloarthritis

Abstract: Introduction:To assess the association between growth differentiation factor-15 (GDF15) and radiographic features including bone marrow edema and bone erosion in Spondyloarthritis (SpA).Methods:Patients with SpA (n = 120) receiving treatment in the Guangdong General Hospital, China, between August 2012 and December 2016 were retrospectively included. Serum of patients and healthy controls (n = 30) were collected and GDF15 levels were measured using ELISA. Inflammation was assessed by C-reactive protein (CRP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
2
7
1
Order By: Relevance
“…Pathway analysis found upregulation in bone and tissue remodelling, which is in line with previous literature, as GDF‐15 has been related to osteoclast differentiation, being attenuated by bone hypoxia 23,50 . Key players in these pathways were osteopontin, IL‐6 and TNFRSF11A.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Pathway analysis found upregulation in bone and tissue remodelling, which is in line with previous literature, as GDF‐15 has been related to osteoclast differentiation, being attenuated by bone hypoxia 23,50 . Key players in these pathways were osteopontin, IL‐6 and TNFRSF11A.…”
Section: Discussionsupporting
confidence: 89%
“…GDF‐15 has been found to suppress osteopontin secretions in fibrotic liver disease, likely acting as a liver protective protein, in line with our findings, as high GDF‐15 was significantly linked to hepatomegaly 54,55 . The bone regulatory effects of GDF‐15 have been linked to bone metastasis in cancer and spondylarthritis, however its exact role in HF remains unclear 24,25,50 …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[13][14][15] Some studies that found GDF-15 levels to be higher in RA and axSpA than in healthy people. 12,16 However, data on this subject are insufficient.…”
mentioning
confidence: 99%